Rediscovering and rethinking Leopold's Green Fire - Rolston, Holmes, 1932-2025, author; Center for Environmental Philosophy, University of North Texas, publisher (Colorado State University. Libraries, 2015)
Lecture given at Utah Valley University, April 4, 2013. Aldo Leopold shot a wolf a hundred years ago, the most iconic wolf kill in conservation history, a shooting now historically confirmed, which after three decades he elevated into his green fire metaphor and symbol. There are tensions. Was Leopold a hypocrite? He spent the rest of his life hunting and trying to produce more game to kill. Thinking like a mountain, thinking big in the big outdoors, there is a dramatic shift of focus from a dying wolf's eyes to a land ethic. Thinking big enough, globally, Leopold's saving wolves, or wilderness, or game management seems simplistic and parochial before global warming or environmental justice. Still, Leopold is on a moral frontier.
Keywords: Leopold, Aldo; wolves; Sand County Almanac; green fire; wilderness; game management; predators; prey; land ethic; respect for life; Earth ethics